IMPLEMENTATION OF THE QUR'AN MEMORIZATION PROGRAM AS A FEATURED PROGRAM IN ACTIVITIES AT MIS ROHMATUL UMMAH - Laila Nasmi; Melpa Hariyanti; Putri Rahma Yani; Putri Yolanda Siregar; Namiroh Lubis (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2026)
This study aims to describe the implementation of the Quran memorization program, a flagship program at MIS Rohmatul Ummah. The program was developed as part of the madrasah's vision of developing a generation of Quranic scholars who love the Quran and possess religious character. This study used a descriptive qualitative approach, with data collection techniques including observation, interviews, and documentation. Data were analyzed descriptively to describe the program's planning, implementation, evaluation, and supporting and inhibiting factors. The results indicate that the Quran memorization program at MIS Rohmatul Ummah was implemented through structured planning, with a target of memorizing a minimum of five juz (juz) for each student by graduation. Program implementation was carried out routinely through muroja'ah (recitation), new memorization lessons, and individual memorization sessions guided by the memorization teacher. Evaluation was conducted continuously by recording students' memorization progress. This program not only improved Quran memorization achievement but also impacted the development of students' religious character, discipline, and responsibility. The program's success was supported by institutional commitment, teacher competence, parental support, and a religious school environment. Thus, the Al-Qur'an memorization program at MIS Rohmatul Ummah can be considered effective as a flagship program of the madrasah.